The Relationship of Thyroid Stimulating Hormone Receptor Antibody (TRAb) Levels to Activity and Clinical Severity of Graves' Ophthalmopathy in RSUP Dr. Sardjito - Putra, Kharisma Wibawa Nurdin Putra; Ikhsan, M. Robikhul; Susanti, Vina Yanti (Acta Interna The Journal of Internal Medicine, 2023)
Background: Graves' disease (GD) is an autoimmune disease that is the most common cause of hyperthyroidism. Thyroid stimulating hormone receptor antibody (TRAb) is a specific biomarker for diagnosing GD. Graves' ophthalmopathy (GO) is the most common extrathyroid manifestation in Graves'. Each GO was assessed for activity and clinical severity for treatment.Objectives: To determine the relationship between TRAb levels and GO clinical activity in Clinical Activity Score (CAS) classification and clinical severity of The European Group on Graves' Orbitopathy (EUGOGO).Methods:  This is a cross-sectional study, conducted from January to August 2021 at RSUP Dr. Sardjito Yogyakarta. 30 newly diagnosed Graves' patients or previously diagnosed with Graves' presented symptoms of hyperthyroidism were included. The patients had TRAb levels > 1.75 IU/L, and diagnosed with Graves' ophthalmopathy based on clinical criteria according to Bartley and Gorman and has not received steroid injections. Serum TRAb examination by electrochemiluminescence immunoassay (ECLIA) method. Clinical activity are assessed with CAS, while severity are assessed with EUGOGO criteria. The data are analyzed using Spearman correlation, multivariate analysis with linear regression and logistic regression.Results: 30 study subjects mean age 35.43 years, female dominant (80%), median GD duration of 13 months. Median TRAb 8.15 IU/L, median CAS score 2 with 46.3% active. Mild severity 40% and moderate-severe 60%. Correlation of TRAb with CAS (r=0.576, p=0.001), EUGOGO (r=0.535, p=0.002). Multivariate analysis of TRAb with CAS (B= 0.076, p=0.01) while EUGOGO (OR=1.198, p=0.045)Conclusion: TRAb is positively correlated with activity and clinical severity of OG.